2006
DOI: 10.1590/s1516-31802006000500004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for death among critically ill patients with acute renal failure

Abstract: CONTEXT AND OBJECTIVE: Acute renal failure is a common medical problem, with a high mortality rate. The aim of this work was to investigate the risk factors for death among critically ill patients with acute renal failure. DESIGN AND SETTING: Retrospective cohort at the intensive care unit of Hospital Universitário Walter Cantídio, Fortaleza. METHODS: Survivors and non-survivors were compared. Univariate and multivariate analyses were performed to establish risk factors for death. RESULTS: Acute renal failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…(14) In our cohort, the patients with AKI were of similar age to those without AKI, and their age was similar to the findings reported by other studies conducted in our region. (7,15,16) The ICU length of stay was similar in patients with and without AKI, most likely due to the severity of pulmonary disease in both groups.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…(14) In our cohort, the patients with AKI were of similar age to those without AKI, and their age was similar to the findings reported by other studies conducted in our region. (7,15,16) The ICU length of stay was similar in patients with and without AKI, most likely due to the severity of pulmonary disease in both groups.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have described AKI, as well as respiratory insufficiency, as independent risk factors for death in critically ill patients. (7,20) It is known that ALI and the consequent hypoxemia, hypercapnia and MV that arise from it worsens renal hemodynamics. This could have increased mortality among the studied cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often this disorder is a marker for underlying pathology, and the most commonly encountered causes of metabolic acidosis are renal insufficiency, sepsis, and diabetic ketoacidosis. Although recent studies showed that metabolic acidosis is associated with high mortality and increased the length of stay in the hospital and ICU (1,2), it remains uncertain whether or not there is a true cause relationship between metabolic acidosis and adverse clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The many risk factors that exist at the ICU stage for donors, including hypotension, pulmonary disease, liver failure, sepsis, hypovolemia, heart failure, bleach injection, and many medications (for example, ACE inhibitors, vasopressors, aminoglycosides, and NSAIDs), can lead to development of AKI. [29][30][31][32][33][34] Kidney donors could potentially present with all of these risk factors. It should also be mentioned that AKI is relatively common in patients with traumatic brain injury (TBI), with an incidence of 9.2%.…”
Section: Discussionmentioning
confidence: 99%